Mycetoma Caused By Streptomyces Somaliensis Involving Female Breast - Maiti PK; Ray A (Wolters Kluwer Medknow Publications, 2000)
A 25 year old female presented with discharging sinuses over breasts for 6 years duration. On the basis of FNAC report suggesting non-caseating tuberculosis, she was treated with ATD for 18 months without success. Subsequently, black grains were detected from the discharge of the sinuses and Str. Somaliensis was grown in culture. The site being a covered area was considered as an extremely rare site for occurrence of the disease.